A Linguistic Inquiry into the Social Media Era Based on the Context of Online Language Variation and Development - Zhao, Yilu (Transactions on Social Science, Education and Humanities Research, 2024)
Against the background of the rapid development of information technology, the Internet and social media have become the main platforms for people's daily communication, which has led to significant language variation. Taking online language variation as an entry point, this paper explores its unique forms and features in the age of social media, including lexical innovations, changes in grammatical structures and the evolution of pragmatic features. By analysing the sociological background of online language variation, the paper reveals the far-reaching impact of technological development, generational differences and regional culture on language change. The study shows that the cross-cultural transmission of Internet language not only enriches the means of expression of modern Chinese, but also promotes the communication and integration of different cultures. This paper further explores the future development trend of Internet language and its impact on language standardisation, education and cultural communication. Through a systematic study of Internet languages, this paper aims to provide new perspectives and methods for understanding the evolutionary patterns of modern Chinese and linguistic research in the social media era, as well as providing useful references for language education and cultural communication practices.